[Aldeyjarfoss] - Streng, Evelyn Fiedler (1975)
Photograph of Aldeyjarfoss Waterfall. The tall waterfall hits the white, rippled water below surrounded by dark rocks. Dark boulders surround the river at the top of the photograph. Mist shoots up from the water below.